Still working while black : the untold stories of student affairs practitioners - Tomlin, Antione D. (Identity & practice in higher education-student affairs., 2023)
"Just as the first edited volume of this book, Working While Black: The Untold Stories of Student Affairs Practitioners, examined student affairs professionals' narratives and how they navigate their professional experiences, this one has a similar aim. This new volume birthed from the overwhelmingly positive feedback and massive interest from other Black professionals needing to share and tell their stories. So, with that in mind, a goal of this book is to share more of the "untold stories of Black student affairs practitioners by Black student affairs practitioners." (Tomlin, 2022, p. X). This book, crafted from an asset-based approach, chapter authors share the challenges and opportunities they have experienced due to being a Black while working as a student affairs practitioner. Additionally, chapter authors provide poignant advice on how current and potential student affairs professionals can successfully navigate the field. Authors within the book are from various student affairs areas and have a wide range of knowledge, expertise, and lived experiences. Such areas include ...I will add areas when chapters are finalized. Given the depth and breadth of experiences and expertise, each chapter will provide poignant suggestions for student affairs practitioners across the nation and institutions looking to understand these experiences to support their employees better. College campuses and spaces operate as models of the greater society. Therefore, all of the challenges and issues of racism, discrimination, and anti-Blackness are present (Rankin et al. 2017). While students experience these challenges and issues first-hand, so do the folx hired to support students, the student affairs practitioners. Kanagala and Oliver (2019) claimed that "for institutions of higher education to be equitable and inclusive, college administrators, faculty, and staff, including student affairs professionals, must attend to the needs of students, especially students with multiple marginalized identities." (p. 410). I argue the same is accurate in creating more equitable and inclusive spaces for student affairs employees. Student affairs practitioners Blackness must be accepted to move toward equity and inclusivity. So, this book roars, "student affairs and white colleagues, please respect our Blackness. Out Blackness is a part of our story, not yours!" (Tomlin, 2022, p. 176). Higher education institutions can learn much from the stories shared in this book that can inform the recruitment and retention of Black professionals. Thus, Still Working While Black: The Untold Stories of Student Affairs Practitioners is a must-read for all higher education professionals and institutions looking for strategies to support Black student affairs practitioners"--